Penjadwalan Untuk Memininimalkan Total Tardiness Dengan Metode Integer Linear Programming - Clara Yessica Livia; Teguh Oktiarso (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Production scheduling is an important thing done in the company so that consumer demand is met on time. PT Mitra Mulia Makmur implements the scheduling principle of First Come First Serve in producing plastic container products. The scheduling applied is not yet effective and efficient because there are some late consumer demands. The delay in consumer demand is due to longer processing time than the specified time limit. In the study using Integer Linear Programming (ILP) method to minimize total tardiness (total tardiness). ILP was chosen as a method of solving delay problems. ILP can help the company’s decision-making process to achieve a purpose function by considering the constraints or constraints in the company. Linear Integer Programming method with the help of LINGO 16.0 software can produce improvements.